THE ROLE OF TECTONIC PROCESSES IN THE GRAVITY FIELD CHANGE OF THE REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
In the article the processes proceeding in the earth's crust and in the upper mantle are examined, which lead changes of physical fields on the earth's surface. Their quantitative assessments are given which can be considered in the forecast of earthquakes.
Keywords: earth’s crust; upper mantle; earthquakes